ANALISIS KESESUAIAN WISATA PANTAI JODO DESA SIDOREJO KECAMATAN GRINGSING KABUPATEN BATANG - Iswaty Chasanah; Pujiono Wahyu Purnomo; Haeruddin Haeruddin (Jurnal Pengelolaan Sumberdaya Alam dan Lingkungan (Journal of Natural Resources and Environmental Management), 2017)
Jodo beach is located in Sidorejo Village, Gringsing District, Batang Regency. The beach is relatively even and has black sand as an attraction. This research was conducted in December 2016 and aimed to determine Jodo beach tourism conformity as beach tourism area in recreation and swimming category. The method used is primary data and method to determine area conformity by multiplying scores and weights obtained from each parameter in beach tourism conformity index, which included depth, beach type, beach width, clarity, current speed, seabed material, harmful biota observation, and the availability of fresh water. In general, all area of Jodo beach have similar characteristics. The result showed that tourism suitability index for beach tourism in station I was 97% S1 (highly suitable), station II was 88% S1 (highly suitable), station III was 82% S2 (suitable), and station IV was 86% S1 (highly suitable). Therefore, the area was suitable for recreational and swimming activity, and continuous development in the Jodo beach tourism area was possible.